PEMBINAAN SPRITUAL CINTA KASIH YESUS KRITUS PADA TNI ANGKATAN DARAT - Riyanto, Agustinus; Helanuswa, Albertus Ganadri (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Indonesian Republic Army have several jobs that require them to work on the front line which is full of risks, dangers, and pressure from work stress and the environment. This activity aims to improve the spirituality of Indonesian Army during 4 days retreat with them of the Jesus Christ spirituality.  The spirituality Jesus Christ retreat was carried out during 9-12 August 2022 at the Wismalat Podomoro, Banyuasin with a total of 45 participants. The material given includes the principle of spirituality, the spirituality of love, being a person full of love and TNI full of love and love. During the activity, the participants participated in the activity until the end, showing enthusiasm for their activities by asking questions and being open to their daily experiences.